2019
DOI: 10.1001/jamasurg.2019.2959
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Recurrence in the Nipple-Areola Complex After Nipple-Sparing Mastectomy With Immediate Breast Reconstruction for Invasive Breast Cancer

Abstract: IMPORTANCE The main concern associated with nipple-sparing mastectomy (NSM) is the risk of local breast cancer recurrence at the retained nipple-areola complex (NAC) consequent to occult nipple involvement. Long-term follow-up data regarding the oncologic safety of modern therapeutic NSM in terms of cancer recurrence at the NAC and survival are limited. OBJECTIVE To assess the incidence, risk factors, treatment, and long-term outcomes associated with cancer recurrence at the NAC in a large series of patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
75
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 25 publications
(44 reference statements)
0
75
0
Order By: Relevance
“…In nine studies, stages 0-I, II, and III were reported in 51.7%, 38.9%, and 9.4% of the cases, respectively (21,24,25,27,29,31,33,35,36). In five studies that reported T-stage, T1, T2, and T3 tumors were in 60.2%, 35.2%, and 4.4% of the cases, respectively (22,26,28,37,38). N0, N1, and N2 disease was reported in 65.1%, 24.8%, and 10% of the patients, respectively (26,28,37,38).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…In nine studies, stages 0-I, II, and III were reported in 51.7%, 38.9%, and 9.4% of the cases, respectively (21,24,25,27,29,31,33,35,36). In five studies that reported T-stage, T1, T2, and T3 tumors were in 60.2%, 35.2%, and 4.4% of the cases, respectively (22,26,28,37,38). N0, N1, and N2 disease was reported in 65.1%, 24.8%, and 10% of the patients, respectively (26,28,37,38).…”
Section: Resultsmentioning
confidence: 95%
“…A total of 457 publications were identified through PubMed and CENTRAL search using the keywords, of which 19 were eligible for inclusion in the final analysis (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). The PRISMA flow chart is presented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…), 61% had NAC involvement. [ 20 ] These findings are considered contraindications to NSM in most literature. Although no patients with nipple discharge had recurrence and metastasis in this study, the relationship between nipple discharge and NSM surgery could not be obtained due to the short follow-up time.…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, quality of life and cosmetic outcomes seems to be similar between BCS and IBR [ 23 ]. NSM with IBR is considered as a valid procedure for prophylactic mastectomy and an acceptable option for BC [ [24] , [25] , [26] , [27] ]. Consequently, the demand of NSM by patients and the propositions of NSM by surgeons increased [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%